Multi-Attribute Decision-Making Methods in Optimizing the Reinsurance Structure for Life Insurance Financing Products: A Case Study of PT Asuransi Jiwa Syariah XYZ - Anindito Dwi Apriano; Lenny Suardi (Eduvest - Journal of Universal Studies, 2026)
Reinsurance structure plays a critical role in balancing risk exposure, financial stability, and profitability in life insurance companies, particularly for portfolios characterized by substantial claim variability and extreme losses. This study aims to determine the optimal combination of quota-share (QS) and excess-of-loss (XL) reinsurance parameters for financing life insurance products at PT Asuransi Jiwa Syariah XYZ. A quantitative case study approach was employed using historical company data, including policies, claims, reinsurance claims, premiums, and reinsurance premiums. Claim distributions were modeled to accommodate the characteristics of both body and tail losses. A total of 1,000 QS–XL alternatives were evaluated using four performance indicators: ruin probability, profit, variance of retained risk, and expected utility. The Complex Proportional Assessment (COPRAS) method was subsequently applied to rank the alternatives according to predetermined company preference weights. The results demonstrate a trade-off between risk retention and profitability, indicating that higher retention may increase profit while simultaneously increasing claim volatility and risk exposure. The COPRAS assessment identified the optimal structure at a quota-share retention proportion of 84.44% and an excess-of-loss retention limit of IDR 105,555,556. This study concludes that the COPRAS-based multi-attribute decision-making framework provides an objective and quantitative approach for selecting a reinsurance structure that balances profitability, utility, risk volatility, and ruin probability.